New taxa and systematic assignments of Madagascan Aradidae(Hemiptera: Heteroptera) - Heiss, E. (Zootaxa, 2010)
In this paper the flat bug genera Jarmilaia Hoberlandt 1957 and Bergrothista Kiritshenko 1959, recorded from Madagascar, are revised. As both genera share distinct metathoracic scent gland canals, a basic character for the classification for the subfamily Mezirinae, these genera, to date treated as Carventinae, are transferred to Mezirinae. Two new species of Jarmilaia, rabitschi n. sp. and zetteli n. sp., and two species of Bergrothista, maculipennis n. sp. and andasibensis n. sp., are recognized and described. For Bergrothista mollis (Hoberlandt 1957) the new genus Parabergrothista n. gen. is erected and a new species P. secunda described and also placed in Mezirinae. A new genus Neobergrothista n. gen. with the species N. rotundiventris n. sp. belongs also to Mezirinae. All taxa are illustrated by colour photographs.